Prenatal care and systemic arterial hypertension previa in women with pre-eclampsia (Revista Contexto & Saúde, 2025)
Hypertensive syndrome in pregnancy has become a serious global health problem, resulting in high hospitalization rates. The objective was to characterize women with preeclampsia treated at a public maternity hospital. This was a retrospective cross-sectional study of pregnant women hospitalized in a public maternity hospital in Piauí between 2017 and 2021, using the International Classification of Diseases (ICD)-10 O14. The sample consisted of 186 medical records. Measures of central tendency, separatrices, simple and relative frequencies, and a chi-square test with p
Keywords: pre-eclampsia; prenatal assistance; pregnant women; hypertension